Emoce: primitivní a kognitivní složka - Polák, Michal (Organon F, 2012)
The paper deals with the problem of emotions. It begins with an analysis of emergence of the emotions according to three types of theories of the emotional process (cognitive, non-cognitive and somatic feedback theories) and shows that any of them has its own difficulties that are not acceptably solved within these theories. Therefore, the paper tries to propose a difference between a raw and cognitive part of an emotion. This difference should be a useful tool in our understanding of emotions.
Keywords: cognition; emotions; somatic feedback theory; two elements of an emotion